1991
DOI: 10.1111/j.1467-8624.1991.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Understanding of Guild and Shame

Abstract: Children's conceptions of the self‐conscious emotions guilt versus shame were investigated. In Study 1, 10–12‐year‐old children answered questions about scenarios that should elicit feelings of guilt and/or shame (moral transgressions and social blunders). In Study 2, 7–9‐ and 10–12‐year‐old children completed a sorting task to ascertain the features they associate with guilt and shame. Feelings of guilt were aroused by moral norm violations. Guilt feelings were also seen as involving an approach‐avoidance con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…We focused on childhood through early adolescence, as the research reviewed previously has indicated that most age-related changes in evaluations of the parental discipline practices under study tend to occur over this age span-such as increasing acceptance of induction (e.g., Paikoff et al, 1988) and a more critical perspective on love withdrawal (e.g., Siegal & Barclay, 1985). We expected developmental changes in understanding of the harmful effects of psychological control across childhood and early adolescence, consistent with research on children's understandings of shame and guilt (Ferguson, Stegge, & Damhuis, 1991). This research has found that younger children (7-to 8-year-olds) are mainly concerned with the external consequences of shame, such as disapproval by authorities or peers.…”
Section: Overview Of the Present Studysupporting
confidence: 76%
“…We focused on childhood through early adolescence, as the research reviewed previously has indicated that most age-related changes in evaluations of the parental discipline practices under study tend to occur over this age span-such as increasing acceptance of induction (e.g., Paikoff et al, 1988) and a more critical perspective on love withdrawal (e.g., Siegal & Barclay, 1985). We expected developmental changes in understanding of the harmful effects of psychological control across childhood and early adolescence, consistent with research on children's understandings of shame and guilt (Ferguson, Stegge, & Damhuis, 1991). This research has found that younger children (7-to 8-year-olds) are mainly concerned with the external consequences of shame, such as disapproval by authorities or peers.…”
Section: Overview Of the Present Studysupporting
confidence: 76%
“…Because the feelings of shame are attributed to global, stable, unchangeable causes, the negative feeling is related to feeling worthless and powerless (Tangney, Wagner, & Gramzow, 1992), and stimulates withdrawal. Despite that shame can be considered an adaptive emotion by fostering conformity and social rules in a group (Ferguson, Stegge, & Damhuis, 1991), an excessive proneness to shame is associated with internalizing problems (e.g., social anxiety, rumination, depression) (e.g., Ferguson, Stegge, Miller, & Olsen, 1999;Tangney et al, 1992). In contrast to shame, guilt is elicited by one's negative evaluation of one's behavior or transgression.…”
Section: Validation Of the Brief Shame And Guilt Questionnaire For Chmentioning
confidence: 98%
“…Although most studies conducted in “Western” contexts have found guilt, not shame, to predict prosocial and restorative tendencies (e.g., Ferguson, Stegge, & Damhuis, 1991; Iyer, Schmader, & Lickel, 2007; Tangney et al, 2007), some recent studies are beginning to uncover a positive side of shame in Western Europe, a relatively individualist context.…”
Section: Cultural Variations In the Behavioral Consequences Of Shamementioning
confidence: 99%